Necropsy-based study on dairy cow mortality—Underlying causes of death - K.A. Hagner; H.S. Nordgren; K. Aaltonen; K. Sarjokari; H. Rautala; T. Sironen; A. Sukura; P.J. Rajala-Schultz (Journal of Dairy Science, 2023)
ABSTRACT: The worldwide problem of increasing dairy cow mortality is widespread in modern production systems, it causes economic losses, and indicates problems with herd health and welfare. Most studies on causes of dairy cow mortality are limited as they are based on secondary register data, or questionnaires for producers or veterinarians, and neither necropsies nor histopathologic analyses are usually performed. For this reason, no definite causes for dairy cow deaths have been determined making it difficult or impossible to implement effective preventive measures. The objectives of this study were to (1) determine the causes of on-farm mortality of Finnish dairy cows, (2) determine the usefulness of routine histopathologic analysis in bovine necropsies, and (3) assess how reliable producers' perception about the cause of death is. Underlying diagnoses of on-farm deaths were determined through necropsy of 319 dairy cows at an incineration plant. The necropsy data were combined with background information obtained from online questionnaires covering cow and herd records. Mastitis was the most common underlying diagnosis of death (26.6%), followed by digestive disorders (15.4%), other known disorders (13.8%), calving-associated disorders (12.2%), and locomotion disorders (11.9%). The underlying diagnoses of death varied during different stages of lactation and with parity. A large proportion of the study cows (46.7%) died during the first 30 d after calving, and of those, 63.6% died during the first 5 d. A routine histopathologic analysis was performed in every necropsy, and it changed the preliminary gross diagnosis in 18.2% of the cases. Producers' perception about the cause of death agreed with the necropsy-based underlying diagnosis of death in 42.8% of the cases. It was most consistent for mastitis, calving disorders, locomotion diseases, and accidents. In cases where producers had no insights about the cause of death, necropsy revealed the final underlying diagnosis in 88.2% of cases, demonstrating the usefulness of necropsy. Based on our findings, necropsies provide useful and reliable information to develop control programs for cow mortality. Including routine histopathologic analysis in necropsies, more accurate information may be obtained. Furthermore, targeting preventive measures on transitional cows may be most effective, as the number of deaths was highest at this time.